Distribution logistics performance: application of a conformity metric between execution and travel plans in a Brazilian logistic company - Freitas, Gabriela de Carvalho (2022)
The wide range of uncertainties occurring in reality on the supply chain makes it extremely difficult to follow the strategic, tactical and operational planning. Transportation often encounters disruptions that prevent them from operating as planned, which affects operating costs and the level of service. To help reduce and manage disruption impacts is to have supply chain robustness and resilience states. Flexible organizations are better able to respond to unexpected events more successfully when compared to their non-flexible counterparts. The flexibility represents the ability to restructure existing capabilities, and assume a different position or configuration to mitigate the magnitude of disruptions. The main purpose of this thesis is to introduce a novel way of measuring travel disruption. The metric compares the level of conformity between travel execution (as-is) and planning. It is validated at a Brazilian logistics company and helps answer whether human feedback increases conformity and reduces future disruption and whether changes in planning have a negative impact on following the plan. The research philosophy is interpretivism with a single case study research strategy. First, primary data are collected through participant observation. Second, a quantitative analysis of the data is performed. The analysis of the metric results made explicit that planning changes does not affect the ability to execute a plan. The execution conformity remains the same regardless of whether or not a plan change occurs, which explains the company's flexibility in adapting to changes. After feedback from the control team to the planning team, future plans were improved and less unconformity to plans were evidenced, so an overall conformity improvement was noted, making clear the importance of the feedback loop to decrease disruptions in planning.